Sinergi Pengawasan Kemitraan Usaha Mikro Kecil Dan Menengah Sebagai Upaya Peningkatan Potensi Dalam Dunia Usaha Ekonomi Kreatif - Suwardiyati, Rumi; Ganindha, Ranitya (Universitas Brawijaya, 2023)
UMKM have demonstrated their various roles in supporting the national economy, but in carrying out their business activities they still experience various obstacles and obstacles, both internal and external. The research aims to produce appropriate concepts in supervision and what institutions are appropriate to optimize UMKM. This research uses socio-legal methods by conducting direct observations to collect data related to the concept of supervisory relationships between institutions that have partnership supervision authority, especially in Malang City. The results of this research are optimizing supervision of UMKN in two ways, namely empowerment through the City Cooperatives and Micro Enterprises Service and empowerment through the Malang City Trade Office. Provide education regarding the importance of understanding partnership agreements. All forms of partnership agreements must be made in writing, the positions of the parties must also be balanced in the partnership agreement. With the existence of these two institutions and education, it is hoped that they can monitor UMKM with the goal to be achieved so that large and small business actors can grow and develop together.